Urea Molasses Multinutrien Blok Sebagai Pakan Tambahan pada Ternak Ruminansia (UREA MOLASSES MULTINUTRIENT BLOCK AS A FEED SUPPLEMENT TO CATTLE) - Yanuartono, Yanuartono; Indarjulianto, Soedarmanto; Nururrozi, Alfarisa; Purnamaningsih, Hary; Raharjo, Slamet (Jurnal Veteriner; Vol 20 No 3 (2019)DO - 10.19087/jveteriner.2019.20.3.445, 2019)
The poor quality crop residues constitute the bulk of dry matter consumed by the ruminants. Like in most developing countries, including in Indonesia, feed shortage is the main constraint to their productivity. During the hot and dry seasons, the available feed resources are not enough in energy and digestion proteins, which are insufficient to maintenance requirements and reducing productivity throughout the year. The use of conventional feedstuffs such as rice brand, pollard, soybean cake, and groundnut cake to enhance production has become inappropriate. These supplements are in short supply owing to increasing demand from agricultural and industrial users. Their exorbitant prices and erratic supply made them too expensive for small-scale farmers to incorporate them into ruminant feeding. Urea Molasses Multinutrient Block (UMMB) is a convenient and inexpensive method of providing a range of nutrients to ruminants. Giving UMMB can improve low-quality feed digestion so in general can improve the performance of livestock such as milk production, weight, BCS and reproductive status. This article aims to evaluation the benefits of a UMMB for feed ruminants.
Keywords: ruminansia, pakan, UMMB, BCS